Research on Russia-America Game: Taking Information Warfare as an Example (Халықаралық қатынастар және халықаралық құқық сериясы, 2023)
In recent years, the soft power contest between the United States and Russia has intensified. Russia is actively developing the news media. During events such as the Syrian war and the U.S. election, Russia has gradually broken the monopoly of the United States and Western countries through mass media and other communication tools. The United States continues to have an advantage in global discursive power, exerting significant influence on world public opinion. The Western countries use modern technologies in the dissemination of information in order to achieve information hegemony. On February 24, 2022, Russia launched a special military operation, which led to a sharp escalation of the situation in Ukraine, and continues to influence the international community. This special operation was the first important military conflict in the era of the mobile Internet that has realized the "integration of time and space". The United States and other Western countries are taking part in the Russian-Ukrainian military conflict, with the exception of direct military action. America and other Western countries are third parties in the Russian-Ukrainian military conflict, but they do not directly participate in hostilities. Currently there is a tough information war with Russia. Since there were initially structural contradictions between Russia and America, and the military factor strengthened them, this conflict is called a new “world war” in the information field. Research on the motivation and characteristics of Russia-America information warfare in this conflict is conducive to a deep understanding of the nature of Russia-Ukraine conflict, the fundamentals of Russia-America game, as well as the direction of Russia-America relationship.Keywords: superpower game, geopolitics, Russia-America relationship, information warfare